2019
DOI: 10.1590/1806-9584-2019v27n254033
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Scientific Participation in Political Science and International Relations in Brazil

Abstract: This article maps the participation of women in Brazilian scientific production in the areas of Political Science and International Relations, from 2006 to 2016. To do so, six indicators were created, to measure women’s participation in the production of master’s dissertations, doctoral theses and scientific papers, as well as their participation as faculty members of graduate programs and their presence on editorial boards of important Brazilian Journals in these fields. The results revealed that, despite an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…However, findings from other countries such as Japan (Kodate & Kodate, 2015; Souma, 2019), Brazil (Mendes & Figueira, 2019), or India (Sinha & Sinha, 2011) suggest that scientific communities still need to put more efforts into creating a healthy environment for women in science. Amidst the coronavirus disease 2019 pandemic, these problems are intensifying and undermining female participation.…”
Section: Introductionmentioning
confidence: 99%
“…However, findings from other countries such as Japan (Kodate & Kodate, 2015; Souma, 2019), Brazil (Mendes & Figueira, 2019), or India (Sinha & Sinha, 2011) suggest that scientific communities still need to put more efforts into creating a healthy environment for women in science. Amidst the coronavirus disease 2019 pandemic, these problems are intensifying and undermining female participation.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial share of the research studies on this topic began to be published in journals linked to the APSA and the ECPR, both of which published a series of works revealing that women are underrepresented in the most prominent political science journals (BREUNING and SANDERS, 2007;CARPIUC, 2016;EVANS and MOULDER, 2011;KONIG and ROPERS, 2018;TEELE and THELEN, 2017;YOUNG, 1995;WILLIAMS et al, 2015). Researchers in peripheral countries replicated these studies and found a similar pattern of inequalities, suggesting that these inequalities exist regardless of the scientific communities' position in the geopolitics of knowledge (CAMPOS, FERES, and GUARNIEIRI, 2017;CARPIUC, 2016;CURTIN, 2013;FERNÁNDEZ, 2006;MENDES and FIGUEIRA, 2019).…”
Section: Studies On Gender Inequalities In Political Sciencementioning
confidence: 97%
“…Other studies corroborate the existence of gender inequalities within political science (DION and MITCHELL, 2019;MATHEWS and ANDERSEN, 2001;REID and CURY, 2019;YOUNG, 1995) To contribute to this debate, we combined two sets of studies that have developed within the Brazilian academic literature and were, until now, poorly articulated: one dedicated to identifying the subfields and methodological preferences within the Brazilian political science community (LEITE, 2016;NICOLAU and OLIVEIRA, 2017), and the other dedicated to providing data for the assessment of gender inequalities in submissions and publications within academic venues (BRINGEL, 2016;MENDES and FIGUEIRA, 2019).…”
Section: Studies On Gender Inequalities In Political Sciencementioning
confidence: 99%
See 2 more Smart Citations